The Relationship between Fast Food Consumption Patterns and Physical Activity with the Incidence of Primary Dysmenorrhea in Adolescent Girls in Classes X and XI at SMK Lab Business School Tangerang - Jeasyana Aprilia Zahri; Nuryanih Nuryanih; Cicirosnita J.Idu Cicirosnita J.Idu (INDOGENIUS, 2026)
Background: Adolescence is a crucial stage of growth marked by physical and hormonal changes, including the onset of menstruation. The consumption of fast food, which is high in fat and free radicals, can increase the production of prostaglandins—compounds that trigger menstrual pain. Meanwhile, a lack of physical activity may reduce blood flow to the uterus, worsening dysmenorrhea. Objective: To determine the relationship between fast food consumption patterns and physical activity with the incidence of primary dysmenorrhea among female adolescents. Methods: This is a quantitative study with a cross-sectional design. The sample consisted of 135 10th and 11th-grade female students selected using total sampling. Data were collected using questionnaires and analyzed using univariate and bivariate methods (Chi-square test). Results: A total of 59.3% of respondents had a high frequency of fast food consumption, and 38.5% engaged in high-intensity physical activity. The Chi-square test showed a significant relationship between fast food consumption (p=0.002) and physical activity (p=0.001) with the incidence of primary dysmenorrhea. Conclusion: There is a significant relationship between fast food consumption patterns and physical activity with the incidence of primary dysmenorrhea among 10th and 11th-grade female students at SMK Lab Business School Tangerang.